Evolution of irradiation-induced strain in an equiatomic NiFe alloy. (November 2017) - Ullah, Mohammad W.; Zhang, Yanwen; Sellami, Neila; Debelle, Aurélien; Bei, Hongbin; Weber, William J.
Abstract: The evolution of irradiation-induced atomic strain in an equiatomic NiFe concentrated solid-solution alloy is investigated using both atomistic simulations and x-ray diffraction analysis. The irradiations are performed using 1.5 MeV Ni ions to fluences ranging from 1 × 10 13 to 1 × 10 14  cm − 2 . The irradiation simulations are carried out by overlapping 5 keV Ni recoils cascades up to a total of 300 recoils. An increase of volumetric strain is observed at low dose, which is associated with production of point defects and small clusters. Relaxation of strain occurs at higher doses, when large defect clusters, e.g., dislocation loops, dominate. Graphical abstract: FIG: (a) Accumulation of point defects in the NiFe alloy with increasing number of cumulative recoils. (b) Change of volumetric strain (εvol  = εxx  + εyy  + εzz ) as a function of number of recoils. The strain values are averaged over the total number of strained atoms in the system. The corresponding dose in displacements per atom (dpa) is also given in both plots.